Scientific Analysis with a Retrospective Method on the Incidence and Severity of Adverse Drug Reactions in Hospitalized Cancer Patients - Diyah Wahyuni; Cinantya Meyta Sari; Budi Suprapti (Postgraduate, University of Mataram, 2024)
Adverse Drug Reactions (ADRs) often result from omissions or inadequate use of preventative measures, making them definitely or probably preventable. Discrepancies between clinical severity and patients' perceptions of ADRs' impact on their well-being highlight the need for targeted interventions. This study focused on the frequency, manifestations, and severity of ADRs from chemotherapeutic agents, utilizing a cross-sectional design with data from ADR reports spanning November 2021 to October 2023 at dr. Saiful Anwar General Hospital, Indonesia. A total of 177 ADRs were analyzed descriptively. Of these, 99 (55.93%) occurred in women, with the highest incidence in the 19–60-year age group (77.40%). The most common malignancies were Chronic Myeloid Leukemia (10.17%), Colorectal Malignancy, and Non-Hodgkin Lymphoma (9.60% each). ADRs related to chemotherapy constituted 41.80%, involving drugs such as cisplatin, oxaliplatin, afatinib, imatinib, and Doxorubicin. The severity distribution was 70.37% mild, 27.16% moderate, and 2.47% severe. Monitoring and reporting these ADRs are crucial for patient safety and preventing recurrence.